Korean presidential election study 1992 - Institute for Korean Election Studies (Institute for Korean Election Studies, 1994)
This survey was carried out the week after the 14th presidential election in Korea, December 1 1992, and include questions on the respondent's interest in the election, exposure to the election campaign, attitude toward the candidates, voting, important issues when selecting a candidate, and experience of bribes and other illegal activities in connection with the election campaign. Background variables include information on gender, age, religion, income, occupation, education and place of residence.

Denna undersökning gjordes veckan efter 14:e presidentvalet I Korea, 1 december 1992 och inkluderar frågor om de svarandes intresse av valet, exponering till valkampanjen, inställning till kandidaterna, röstning, viktiga frågor i valet av en kandidat, och erfarenhet av mutor och andra illegala aktiviteter i samband med valkampanjen. Bakgrundsvariabler inkluderar information om kön, ålder, religion, inkomst, yrke, utbildning och bostadsort.
Korean presidential election study 1992
Keywords: internal politics; inrikespolitik; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap